The seismic Lg waves and their propagation along the granitic layer of the crust of Indian Sub-Continent (MAUSAM, 1961)
Guided or channel waves of the Lg type were observed in Colaba seismcgrams due to an earthquake and its, aftershock originating in Nepal, Similar observations are also available from another earth-quake having its origin in Assam-Bhutan border.  No such waves were, however, recorded by similar seismographs at Shillong and Madras.  They are also absent in the records of Quetta (Pakistan) seismographs having different characteristics. Lg waves are also absent in the records of the shocks criginating in the zones to the north of the Himalayas, The geological significance of the existence and non-existence of Lg waves in earthquake records is discussed. Similarity between ordinary microseisms of 4 to 10 seconds periods is also considered and an explanation has also been suggested why microseisms could propagate through the ocean bottom while the Lg waves are completely deleted during its passage through the oceanic path. The well defined Lg and Rg phase in records of the Assam-Bhutan border shock probably goes to show the importance of the focus in the granitic layer for the generation of this type of guided waves.